Digital Transformation, Green Finance and Fintech in a Sustainable Digital Economy - Edi Suranta Tarigan; Harjum Muharam; Wisnu Mawardi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the promotion of a green digital economy and evaluate the role of digital transformation, green finance, and financial technology (Fintech) in supporting a sustainable economy. Using a quantitative method with a purposive sampling technique, 100 respondents were obtained through a survey. The analysis was carried out descriptively and using the Partial Least Squares (PLS) approach as a variance-based structural modeling technique. The results of the study indicate that digital transformation, green finance, and Fintech each have a positive and significant effect on the development of a sustainable economy. These findings emphasize the importance of integrating digital innovation and green financial strategies in supporting long-term sustainability. This study recommends that further studies use different groups of respondents and apply alternative analytical methods to broaden the perspective. Thus, further research can provide a more comprehensive understanding of the contribution of digital and financial innovation to achieving a green digital economy.